Pengaruh Profitabilitas, dan Solvabilitas terhadap Harga Saham: Studi Kasus Industri Perbankan yang Terdaftar di BEI pada Periode 2016-2020 - Sumarni , Marini; Nirmasari, Dian; Mas’ud, Busrin Raihana (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study investigates the impact of profitability and solvency on stock prices, with a specific focus on the banking sector listed on the Indonesia Stock Exchange (IDX) over the period 2016-2020. Adopting a quantitative research approach, the study utilizes secondary data derived from the financial statements of 32 publicly listed banking institutions. The analysis is conducted using multiple regression techniques to examine the relationship between the variables. The findings reveal that both profitability and solvency exert a positive and statistically significant influence on stock prices, suggesting that these financial indicators play a critical role in determining market valuation within the Indonesian banking sector.